The effect of courtyard designs on young people, which have been made according to different functional preferences: Barti{dotless}n university (Turkey) - Bekci, Banu; Taşkan, Gaye; Bogenç, Çiğdem (WFL Publisher Ltd., 2013)
Besides the use of gardens of big buildings serving for different functional purposes, which are used by a great number of users, also the use of their courtyards has an important place in the socialization of people. These places, which are an indispensable element of architecture, constitute the core of these buildings, and on the other hand, provide the users with many different functional usages, as relaxation, working and living places. In the study, the usability and visual quality of the courtyard in Barti{dotless}n University's Faculty of Forestry has been analyzed. The study consists of the stages of the visual evaluations of the studies intended for ascertaining (i) how the young people studying at Barti{dotless}n University evaluate the campus area (ii) expectation of the users of the Faculty of Forestry building (academic, administrative staff, landscape architecture, forest industry engineering student, forest engineering student) from the courtyard, and (iii) courtyard usage containing different functional usages (for living, exhibition and visual purposes). In this context, the survey was applied to 205 users, and the results were examined by correlation, variance and Duncan analyses. In the light of the data obtained, a statistically significant correlation was found between the user groups, user preferences, and the visual quality of the projects (P < 0.05). The fact that the young people's desire of spending their spare time in the actively used places shows parallelism with their preference of functionality also in the use of courtyard was determined by Semantic Differential Technique. As a result, some determinations were made for the environmental quality of the use of courtyard space, and recommendations for the young people's preferences regarding the use of space were developed. © 2018 Elsevier B.V., All rights reserved.
Keywords: Adolescents; Courtyard; Gender; Sociology; Young People